The purpose and effectiveness of doping testing in sport - Fredrik Lauritzen; Anders Solheim (Frontiers Media S.A., 2024)
Maintaining an effective testing program is critical to the success and credibility of the anti-doping movement. However, a low detection ratio compared to the assumed real prevalence of sport doping has led some to question and criticize the effectiveness of the current testing system. In this perspective article, we review the results of the global testing program, discuss the purpose of testing, and compare benefits and limitations of performance indicators commonly used to evaluate testing efforts. We suggest that an effective testing program should distinguish between preventive testing and testing aimed at detecting the use of prohibited substances and prohibited methods. In case of preventive testing, the volume of the test program in terms of number of samples, tests and analyses is likely to be positively related to the extent of the deterrent effect achieved. However, there is a lack of literature on how the deterrent effect works in the practical context of doping testing. If the primary goal is to detect doping, the testing must be risk- and intelligence-based, and quality in test planning is more important than quantity in sample collection. The detection ratio can be a useful tool for evaluating the effectiveness of doping testing, but for the calculation one should take into account the number of athletes tested and not just the number of collected samples, as the former would provide a more precise measure of the tests' ability to detect doping among athletes.